2023
DOI: 10.3390/pr11072064
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Characterization of Bromelain from Pineapple Core: A Strategy for Pineapple Waste Valorization

Abstract: Bromelain is a mixture of cysteine endopeptidase usually extracted from pineapple juice and is used for the treatment of various human diseases and in industrial applications. Bromelain demand is quickly increasing, and its recovery from pineapple residues appears to be a sustainable waste management strategy. Pineapple core is among the most significant waste materials in the production of canned pineapple and is richer in bromelain than other pineapple residues. In this project, we compared the enzymatic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In this work, we scaled up a previously reported lab-scale process [ 15 ]. Thoroughly washed, size-selected pineapples ( Ananas comosus L.) at a uniform ripening stage were cut into fruit slices (rings) using the GINACA–TFGK-5, a processing machine obtained from Tropical Food Machinery srl (Busseto, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…In this work, we scaled up a previously reported lab-scale process [ 15 ]. Thoroughly washed, size-selected pineapples ( Ananas comosus L.) at a uniform ripening stage were cut into fruit slices (rings) using the GINACA–TFGK-5, a processing machine obtained from Tropical Food Machinery srl (Busseto, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…Other researchers have suggested that stem bromelain's enzymatic activity is higher than fruit bromelain's. Stem bromelain has a molecular weight of 27 kDa, while fruit bromelain has molecular weights between 19 and 23 kDa [27,28]. According to Chakraborty et al [27], multiple proteinase fractions have different molecular weights in each plant portion with slight changes in the amino acid terminals.…”
Section: Phase Iii-production Of Bromelain Powders From Pineapple Ste...mentioning
confidence: 99%